1993
DOI: 10.1242/jcs.105.3.655
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of band 3 in hereditary ovalocytic red blood cell membranes Electron microscopy and protein rotational diffusion studies

Abstract: Microaggregation of band 3 proteins in hereditary ovalocytic membranes was investigated by rotational diffusion measurements and by electron microscopy. It was previously shown that band 3 in ovalocytic membranes has decreased rotational mobility compared with band 3 in normal cells (Tilley, L., Nash, G.B., Jones, G.L. and Sawyer, W.L. (1991) J. Membr. Biol. 121, 59–66). This result could arise from either altered interactions with cytoskeletal proteins or from band 3 microaggregation. In the present study it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Other evidence also suggests the band 3 in SAO membranes has a greater tendency to aggregate than normal band 3 and greater propensity to form tetramers (16,18). Freeze-fracture electron micrographs of SAO red cells also show the presence of unusual linear microaggregates of intramembranous particles that most likely contain band 3 (32). Table 2 and Figure 4 show that the normal band 3 sites not cleaved in band 3 of SAO membranes are distributed over the entire band 3 molecule.…”
Section: Discussionmentioning
confidence: 95%
“…Other evidence also suggests the band 3 in SAO membranes has a greater tendency to aggregate than normal band 3 and greater propensity to form tetramers (16,18). Freeze-fracture electron micrographs of SAO red cells also show the presence of unusual linear microaggregates of intramembranous particles that most likely contain band 3 (32). Table 2 and Figure 4 show that the normal band 3 sites not cleaved in band 3 of SAO membranes are distributed over the entire band 3 molecule.…”
Section: Discussionmentioning
confidence: 95%
“…Band 3 rotational mobility is constrained in normal RBC membranes by low-affinity and high-affinity binding interactions (24,31,33,34,(41)(42)(43)(44)(45)(58)(59)(60). The rotationally immobile band 3 fraction apparently represents individual band 3 molecules bound with high affinity to ankyrin.…”
Section: Discussionmentioning
confidence: 99%
“…The rapidly rotating band 3 fraction is presumed to consist of free band 3 dimers, tetramers, and possibly higher order oligomers (34,36). In some pathologic RBCs, the rotationally immobile band 3 fraction contains clustered or linearly aggregated band 3 molecules (31,(41)(42)(43), but in normal cells this fraction is likely to represent band 3 molecules bound with high affinity to ankyrin. The slowly rotating band 3 fraction is less well characterized, however.…”
mentioning
confidence: 99%
“…The decrease in ATP levels during in vitro storage was hypothesized to be an initial step in membrane vesiculation and band 3 protein rearrangement [ 19 ]. Previous data showed that clustering and microaggregation of the Band 3 protein were observed during cold storage [ 40 ]. Karon et al reported that storage at cold temperatures altered Band 3 oligomericity in the RBC membrane [ 16 ].…”
Section: Discussionmentioning
confidence: 99%